2007
DOI: 10.1152/ajpheart.01164.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of burn-related changes in contractility and its prevention by mesenteric lymph ligation

Abstract: Major burn injury results in impairment of left ventricular (LV) contractile function. There is strong evidence to support the involvement of gut-derived factor(s) transported in mesenteric lymph in the development of burn-related contractile dysfunction; i.e., mesenteric lymph duct ligation (LDL) prevents burn-related contractile depression. However, the cellular mechanisms for altered myocardial contractility of postburn hearts are largely unknown, and the cellular basis for the salutary effects of LDL on ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…This notion that gut-derived factors carried in the mesenteric lymph can cause acute myocardial dysfunction is further supported by our studies in a burn model where LDL prevented ex vivo burn-induced myocardial depression and where burn lymph recreated this myocyte depressant state in vitro (20,32). On the basis of our previous burn studies showing that the contractile dysfunction of postburn hearts is linked with a decrease in ventricular myocyte Ca 2ϩ transients caused by a decrease in the Ca 2ϩ entry through L-type Ca 2ϩ channels (20), we examined Ca 2ϩ responsiveness of the T/HS hearts.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This notion that gut-derived factors carried in the mesenteric lymph can cause acute myocardial dysfunction is further supported by our studies in a burn model where LDL prevented ex vivo burn-induced myocardial depression and where burn lymph recreated this myocyte depressant state in vitro (20,32). On the basis of our previous burn studies showing that the contractile dysfunction of postburn hearts is linked with a decrease in ventricular myocyte Ca 2ϩ transients caused by a decrease in the Ca 2ϩ entry through L-type Ca 2ϩ channels (20), we examined Ca 2ϩ responsiveness of the T/HS hearts.…”
Section: Discussionsupporting
confidence: 72%
“…The mechanisms by which these lymphatic borne factors are produced as well as the organs involved in their production seem to involve pancreatic enzymes interacting with the ischemic gut (1,14,28). Furthermore, our recent studies measuring cardiac contractility in isolated hearts and myocytes from rats subjected to burn injury (20,32) have shown that mesenteric lymph generated following burn injury directly causes changes in cardiac contractility, thereby supporting the role of mesenteric lymph as a key factor involved in regulating myocardial contractile dysfunction.…”
mentioning
confidence: 91%
“…Further, mesenteric lymph collected from mice following trauma-hemorrhagic shock (T/HS) and injected into trauma-sham shock (T/SS) mice induces lung injury and demonstrates the same toxic properties of intestinal lymph seen in T/HS (13). Additionally, ligation of the mesenteric lymph duct in either T/HS or in burn injury prevents injury-induced decreases in cardiac contractility and cardiac output (14–16). Perhaps most importantly, ligation of the mesenteric lymphatic duct improves survival in multiple animal models of critical illness (5;17).…”
Section: Evolution Of the Concept Of The Gut As The Motor Of Modsmentioning
confidence: 99%
“…Our most recent study has demonstrated that burn trauma induces leaky sarcoplasmic reticulum (SR), leading to partial depletion of SR Ca 2+ content and the resulting diminished systolic Ca 2+ transient and contractile deficit (5). In contrast to the findings on ventricular myocytes isolated from burn-traumatized heart, Yatani and coworkers (6) demonstrated that mesenteric lymph from rats with thermal injury significantly increased the myocyte contractility and systolic Ca 2+ transient in cardiomyocytes isolated from normal rat heart, despite that all the evidence heretofore supports that burn lymph plays an important role in inducing burn-generated cardiac dysfunction (4,7). The contradictory results obtained from these two classes of experiments arouse 2-fold concerns: first, whether the process of cardiomyocyte isolation and the environment for the isolated cells, which is free of burn-generated detrimental factors, change and/or mask some alterations in excitation-contraction (EC) coupling presented in burn-traumatized cardiomyocytes in vivo; second, how does the burn injuryYrelated humoral environment act on the development of burn-generated cardiac dysfunction, and what are the underlying mechanisms?…”
Section: Introductionmentioning
confidence: 97%